2022
DOI: 10.1002/slct.202200307
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Role of Metals in Mononuclear Metal‐Complexes for Chemodosimetric Detection of S2− from aqueous medium: Experimental and DFT Corroboration with Real‐Field Application

Abstract: Herein, we have reported two isostructural mononuclear metal complexes [M(HL)2(ClO4)2], wherein, M= Co2+ (viz. SN‐1) and Ni2+ (viz. SN‐2) and HL is NNO donor Schiff‐base ligand i. e. ((E)‐2‐methyl‐2‐((pyridin‐2‐ylmethylene)amino)propan‐1‐ol) for unveiling as molecular sensor for S2− (sulphide) like hazardous entity. The molecular probes have been characterized by SCXRD, 1H‐NMR, FT‐IR, HRMS etc. X‐ray diffraction studies confirm the mono‐nuclear structures of both the complexes. Interestingly, SN‐1 exhibited re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…5 From recent research activities it is noticeable that metal–organic frameworks and their hybridized nanostructures ( e.g. , metal oxides and porous carbons) 6 have attracted significant attention in the formation of electronic devices 7 and fuel cells, 8 thin-film devices, 9 super capacitors, 10 magnets, 11 sensors 12 a – c ( vide Scheme 1a), Li-ion batteries, 13 and catalysts, 14 as well as for biomedical applications, 15 drug loading and delivery 16 etc. MOF materials have been explored efficiently in the domain of sensors due to their crystalline nature and tailor-made design strategies, which facilitate the mechanistic pathways of host–guest interactions at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…5 From recent research activities it is noticeable that metal–organic frameworks and their hybridized nanostructures ( e.g. , metal oxides and porous carbons) 6 have attracted significant attention in the formation of electronic devices 7 and fuel cells, 8 thin-film devices, 9 super capacitors, 10 magnets, 11 sensors 12 a – c ( vide Scheme 1a), Li-ion batteries, 13 and catalysts, 14 as well as for biomedical applications, 15 drug loading and delivery 16 etc. MOF materials have been explored efficiently in the domain of sensors due to their crystalline nature and tailor-made design strategies, which facilitate the mechanistic pathways of host–guest interactions at the molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…They have also exhibited many interesting, challenging, and diverse coordination chemistry. Until now, considerable research and development of transition metal complexes is ongoing because of their tremendous applications and advances in the field of bioinorganic chemistry, medicinal chemistry, drug delivery, catalysis, gas sorption, sensing, and molecular magnetism. , These applications and advances have rekindled our interest in the synthesis and physicochemical characterization of different transition metal complexes. Among them, high-spin Co­(II) complexes are very popular to the coordination/material chemists owing to their interesting magnetic properties. They are good candidates that act as single-molecule magnets , and single-chain magnets , because of their half-integer spins ( S = 3 / 2 ) and sizable magnetic anisotropy arising from spin-orbit coupling among the ligand field states. Several studies on mono- and dinuclear Co­(II) complexes have shown the impact of coordination number, geometrical arrangement, and identity of the ligand on zero-field splitting parameters and magnetic relaxation rates. In this context, the dinuclear Co­(II) complexes bearing alkoxide/phenoxide/hydroxide bridges have attracted much attention in recent times. Particular interest has been focused on the relationship between their structures and magnetic properties in order to understand the detailed magneto-structural correlations. It should be mentioned that the dimetallic complexes constitute an emerging and sophisticated subgroup of compounds within the family of multinuclear metal assemblies.…”
Section: Introductionmentioning
confidence: 99%